2019
DOI: 10.3390/ijerph16224472
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Inhibitory Effect of Calcium Polypeptides on Cd Enrichment of Brassia campestris L.

Abstract: Most cadmium-polluted farmland and land surrounding mining areas are difficult to repair and control, seriously threatening the food safety of the crops planted in these regions. As an essential element for plant growth, calcium plays an important role in stress-resistance regulation. In this study, Brassia campestris L. was used as the experimental material and polluted soil with cadmium was used as the experimental soil sample, to explore the competition inhibition of calcium polypeptide application on the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 56 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…Although a similar significant decrease in Cd accumulation in Boehmeria nivea was observed under 5 mM Ca treatment, a contrasting significant increase in Cd uptake and accumulation was unraveled under 1 mM Ca treatment [110], supporting the dose-dependent effect of Ca on Cd uptake in plants. The repression of Cd accumulation by Ca supplements was significant at 2-3 mM; suppression reached its peak when the Ca concentration was at 5 mM [47]. Similar reductions in Cd absorption and accumulation in the wheat and soybean roots were observed at Ca concentrations of 1 mM and 10 mM [111].…”
Section: Calcium (Ca)mentioning
confidence: 54%
See 2 more Smart Citations
“…Although a similar significant decrease in Cd accumulation in Boehmeria nivea was observed under 5 mM Ca treatment, a contrasting significant increase in Cd uptake and accumulation was unraveled under 1 mM Ca treatment [110], supporting the dose-dependent effect of Ca on Cd uptake in plants. The repression of Cd accumulation by Ca supplements was significant at 2-3 mM; suppression reached its peak when the Ca concentration was at 5 mM [47]. Similar reductions in Cd absorption and accumulation in the wheat and soybean roots were observed at Ca concentrations of 1 mM and 10 mM [111].…”
Section: Calcium (Ca)mentioning
confidence: 54%
“…A decrease in the root Cd concentration of Brassica juncea was observed under a Ca + Cd combination rather than Cd alone [109]. The Ca polypeptide not only promoted the plant growth of the Brassica campestris but also showed competitive inhibition of Cd uptake in plants [47].…”
Section: Calcium (Ca)mentioning
confidence: 91%
See 1 more Smart Citation
“…38 Ca is an important macronutrient for plants and plays a significant regulatory role in the growth and development of plants and in the response to abiotic stress. 39 The positive effects of Ca on plant growth under Cd exposure have long been confirmed as a result of Cd−Ca antagonism. 40−42 This study also showed similar results that 10 mM Ca ameliorated the toxicity of Cd, whereas the toxicity was enhanced when supplemented with 0.5 mM Ca (Figure 1).…”
Section: ■ Discussionmentioning
confidence: 99%